Citizen Participation, Associations, and Conflict: The Transformation of Valparaíso’s Former Prison. - van Diest, Camila (Latin American Research Review, 2020)
After a long period of dictatorship in Latin America, the quality and deepening of democracy have been associated with citizen participation. This article examines the social uses of the notion of participation beyond an exclusively institutional dimension. Starting from the example of the transformation of Valparaíso’s former prison into a cultural space, initiated in 1999, this article studies participation in light of the fluctuating relationships to politics that different actors maintain. It examines how the former prison was transformed into a cause as part of a broader response to a neoliberal urban project and top-down practices. Further, this work analyzes the diverse experiences of commitment among the artists occupying the former prison, highlighting the tensions and dilemmas associated with the exercise of politics in a conflictual context.